1996
DOI: 10.1021/om9600248
|View full text |Cite
|
Sign up to set email alerts
|

Mes2GeCPAr:  The First Germaphosphaallene

Abstract: The first germaphosphaallene, 3, has been obtained by debromofluorination of the (fluorogermyl)bromophosphaalkene 7 and characterized by 31P NMR (240 ppm) and 13C NMR (280.9 ppm for the allenic carbon) at low temperature. Methanol and methyllithium react exclusively with the GeC double bond to afford the corresponding adducts 9 and 10. In the absence of a trapping reagent, 3 gives two types of dimer, 13a (involving two GeC bonds) and 14a (involving one GeC and one PC bond).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(31 citation statements)
references
References 23 publications
3
28
0
Order By: Relevance
“…These properties of 5 c ± e resemble those of the reported stannaketenimine, [18] and indicate sharp contrasts to those of 1-phospha-3-silaallene [19] and 1-phospha-3-germaallene, [20] which reportedly have cumulative-compound character.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…These properties of 5 c ± e resemble those of the reported stannaketenimine, [18] and indicate sharp contrasts to those of 1-phospha-3-silaallene [19] and 1-phospha-3-germaallene, [20] which reportedly have cumulative-compound character.…”
Section: Resultsmentioning
confidence: 65%
“…Recently, Escudie ¬ et al have reported the spectroscopic observation of two new species having an > MCE-(M Group 14 element; E Group 15 element) structure, for example, 1-phospha-3-silaallene [Tip(Ph)SiCPMes*] (Tip 2,4,6-(iPr) 3 C 6 H 2 ; Mes* 2,4,6-(tBu) 3 C 6 H 2 ) [19] and 1-phospha-3-germaallene [Mes 2 Ge C PMes*]. [20] These compounds have been found to represent allenic character in contrast to the stannaketenimine.…”
Section: Introductionmentioning
confidence: 99%
“…The down-field shift for the central sp carbon has been also observed for 1-silaallene 200 (δ c = 226) 8 and germaphosphaallene 202 (δ c = 281) 122 . Although 207 can be trapped with methanol, mesitonitrile oxide and elemental sulfur to give the corresponding adducts 208-210, it slowly undergoes an intramolecular cyclization in solution at room temperature to give compound 211 (Scheme 64) 25,123 .…”
Section: E Reactivities Of Heavy Ketonesmentioning
confidence: 57%
“…Although the generation of 202 was confirmed by 13 C and 31 P NMR at −40°C, 202 dimerized at room temperature to afford two types of dimers, i.e. 203 and 204 (Scheme 62) 122 . This result shows that the combinations of the substituents on the germanium and phosphorous atoms were not bulky enough to prevent dimerization of 202.…”
Section: E Reactivities Of Heavy Ketonesmentioning
confidence: 99%
See 1 more Smart Citation